The Influence of Employee Competency and Motivation on Performance Through Job Satisfaction as an Intervening Variable - Harahap, Fahmi Salim; Dudung Hadiwijaya; Priyo Susilo (Quantitative Economics and Management Studies, 2024)
The purpose of this study is to determine the effect of employee competence, and motivation on performance, with job satisfaction as an intervening variable. This study used a quantitative–associative approach, and the data collection method used non-probability sampling techniques with purposive sampling types. Data distribution using questionnaires from Google Form to employees serving at the Directorate General of Customs and Excise of Banten Regional Office. Smart-PLS software is used to analyze the reliability of PLS-SEM-based models. Based on the results of Structural Equation Modeling (SEM) analysis and hypothesis testing in this study, conclusions were drawn. Based on the results of the tests that have been carried out, it can be concluded that; The test results prove that Motivation is proven to have a positive and significant influence on Job Satisfaction. The test results prove that Competency is proven to have a positive and significant influence on Job Satisfaction. The test results prove that Motivation is proven to have a positive and significant influence on Job Satisfaction.